Clinical value of circulating splicing factors in prostate cancer: SRRM1 as a novel predictive biomarker and therapeutic target - Antonio J. Montero-Hidalgo; Enrique Gómez-Gómez; Manuel Galán-Cañete; Francisco Porcel-Pastrana; Jesús M. Pérez-Gómez; María Ortega-Bellido; Julia Carrasco-Valiente; Laura Chamorro-Castillo; Juan P. Campos-Hernández; Oriol A. Rangel-Zuñiga; Teresa González-Serrano; Rafael Sánchez-Sánchez; et al. (Molecular Therapy: Oncology)
Prostate cancer (PCa) is the second most common cancer among men worldwide. The main screening tool remains the prostate-specific antigen (PSA), which shows significant limitations, including poor sensitivity/specificity. Therefore, establishing accurate non-invasive diagnostic biomarkers remains an unmet clinical need in PCa. In this context, the splicing process dysregulation represents a PCa hallmark. Here, plasma SRRM1, SNRNP200, and SRSF3 levels, previously identified to play a pathophysiological role in PCa, were determined in control individuals (n = 40) and PCa patients (n = 166). We found that plasma SRRM1 and SNRNP200 levels were elevated in PCa patients and discriminated between control individuals and PCa patients. High plasma SRRM1 levels were associated with a shorter castration-resistant PCa-free survival and correlated with androgen-receptor (AR)/AR-splicing variant 7 (AR-V7) expression levels and activity in PCa tissues. Therefore, the functional and molecular effects of in vivo SRRM1 silencing were then tested in 22Rv1-derived xenograft tumors. In vivo SRRM1 silencing reduced aggressiveness features and altered AR/AR-V7 activity. Our data reveal that SRRM1 holds potential as a non-invasive diagnostic and prognostic biomarker and novel therapeutic target in PCa, offering a clinically relevant opportunity worth exploring in humans.